Impacts of School-Based Outdoor Pedagogical Training Programme on the Teaching Practices of Pre-Primary School Teachers in Oyo State, Nigeria - Leigh, F; Ayodele, A; Adekoya-Olapade, O (African Journal of Education and Practice, 2024)
Purpose: The pedagogical potential of outdoor learning in fostering the well-being and holistic development of children have been extensively documented in literature. Most pre-primary school children in Nigeria are however rarely exposed to outdoor learning experiences, owing probably to the inadequacies in knowledge and expertise among pre-primary school teachers. This study developed, implemented and determined the effectiveness of school-based experiential outdoor pedagogical training programme on the teaching practices of pre-primary school teachers in Oyo State, Nigeria. Methodology: The study adopted explanatory sequential design of mixed research methods, where qualitative data supported quantitative findings and provided evidences of the effectiveness of the training programme on outdoor teaching practices. The study used outdoor teaching competencies of the teachers, before and after the training, to provide quantitative evidence as well as interviews to elucidate the perspectives of the teachers on the impact of the training. The participants were (n = 36) pre-primary school teachers who were selected through multi-stage sampling technique across the three Senatorial districts in Oyo State, Nigeria. Experts in outdoor learning in early childhood facilitated the training. The participants were exposed to various critical aspects of their role in facilitating meaningful and enriching outdoor learning experiences for pre-primary children. The participants were engaged in hands-on training with various aspects of effective implementation of the early childhood curriculum in the outdoor environment. Aspects covered included lesson planning, sourcing lesson materials, organization of learning environment, instructional approaches and techniques, assessment and safety management, among others. The study was carried out between September, 2022 and June, 2023. Findings: The study found a variety of improvement in the outdoor teaching practices and learning opportunities for the children. The training showed positive effects on teaching practices and the overall performance of the teachers. The teachers showed increased skillfulness in lesson planning, instructional effectiveness, creativity and innovation in facilitating learning as well as deployment of varieties of teaching methods. The teachers broadly reported positive perspective of the training and believed it was helpful to their teaching practices. In addition, the teachers agreed that the training increased their confidence and expertise to engage children in quality outdoor learning as well as improved children's participation and enthusiasm for learning. Lack of policy support, parental concerns, time and availability of resources were some of the barriers reported by the teachers in the study. Unique Contribution to Theory, Practice and Policy: This study was anchored on experiential theory which emphasized the transformational effect of learning through direct experience, reflection and active experimentation. The findings appeared to lend support to the realms of theory, practice and policy within the domains of early childhood education. It enriched theoretical understanding by offering concrete, real-world applications of outdoor learning concepts, thereby, fostering a deeper comprehension of learning in the practical setting. It also provided pre-primary teachers with practical tools and strategies to effectively implement outdoor learning methodologies, thereby, promoting a more holistic and experiential approach to early childhood education. The study similarly provided a basis for the integration of outdoor pedagogy in the formal educational structure, emphasizing the significance of nature-based education and, suggesting the need for a broader integration of outdoor strategies in the context of educational policy development in Nigeria.